International Practice of Inflation Targeting: Israel as a Case Study - A. V. Fedorchenko; F. V. Malahov (Vestnik MGIMO-Universiteta)
The article deals with the transition to inflation targeting, which is a flexible and relatively new method of monetary policy. The Israeli experience in this field is analyzed. The paper shows that, after long periods of high inflation and disinflation the Bank of Israel has adopted the most efficient and painless for other macroeconomic objectives tools.